Six new species of the genus Exocelina Broun, 1886 from Wano Land, New Guinea (Coleoptera, Dytiscidae, Copelatinae) - Helena Shaverdo; Michael Wild; Bob Sumoked; Michael Balke (ZooKeys, 2017)
Six new species of New Guinea Exocelina Broun, 1886 are described in this paper: E. iratoi sp. n., E. likui sp. n., E. pui sp. n., E. pulukensis sp. n., E. tomhansi sp. n., and E. wigodukensis sp. n. Although different morphologically, together with Exocelina ascendens (Balke, 1998), E. bagus (Balke & Hendrich, 2001), and E. ransikiensis Shaverdo, Panjaitan & Balke, 2016, they are found to form a monophyletic clade and be closely related to representatives of the E. ekari-group, based on preliminary analysis of sequence data. An identification key to the species is provided, and important diagnostic characters are illustrated. The present data on the species’ distribution show that most of them are local endemics.